2017
DOI: 10.1159/000468925
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ineffective Esophageal Motility on Gastroesophageal Reflux Disease

Abstract: Background/Aims: Ineffective esophageal motility (IEM) is the most common gastrointestinal motility disorder. Studies have reported that IEM is related to gastroesophageal reflux disease (GERD). However, the relationship between IEM and GERD remains uncertain. This study aims to clarify this relationship retrospectively. Methods: We analyzed 195 subjects who underwent high-resolution manometry between January 2011 and September 2016. Of these subjects, 72 had normal esophageal motility (NEM) and 26 had IEM. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
1
19
1
1
Order By: Relevance
“…[21] However, other studies have reported no association between IEM and GERD. [22] This is in agreement with our finding of no significant correlation among esophageal motility disorders, GIP and PP levels, and AET. The CFV value was higher in the AET– group; however, the role of CFV is not emphasized in the CC ver.…”
Section: Discussionsupporting
confidence: 93%
“…[21] However, other studies have reported no association between IEM and GERD. [22] This is in agreement with our finding of no significant correlation among esophageal motility disorders, GIP and PP levels, and AET. The CFV value was higher in the AET– group; however, the role of CFV is not emphasized in the CC ver.…”
Section: Discussionsupporting
confidence: 93%
“…[ 9 ] Nevertheless, while a significant relationship was found between IEM and GERD in some studies, no relationship was found in others. [ 10 12 ] As a result, although pathological esophageal acid reflux and IEM are frequently associated, the presence of IEM is not considered pathognomonic for GERD. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…Ineffective esophageal motility is frequently seen in patients with GERD [12]. However, the association between GERD and IEM is yet not fully understood and discussed very controversially [13, 14]. Notably, there are numerous reports, which show a possible connection between the IEM and impaired mucosal integrity caused by GERD [12, 15, 16].…”
Section: Discussionmentioning
confidence: 99%